Microneedles in Clinical Practice-An Exploratory Study Into the Opinions of Healthcare Professionals and the Public - Birchall, James C; Clemo, Rachel; Anstey, Alexander; John, Dai N (Pharmaceutical research, 2011)
Purpose Microneedles are being developed to administer vaccines and therapeutics to and through skin. To date there has been no qualitative or quantitative research into public and health professionals' views on this new delivery technique. Methods Focus groups (n=7) comprising public and healthcare professionals were convened to capture the perceived advantages for, and concerns with, microneedles. Discussions were audio-recorded and transcribed. Transcript analysis identified themes that were explored using a questionnaire identifying consensus or otherwise. Results Participants identified many potential benefits of the microneedle delivery system, including reduced pain, tissue damage and risk of transmitting infections compared with conventional injections, as well as potential for self-administration (subject to safeguards such as an indicator to confirm dose delivery). Delayed onset, cost, accurate and reliable dosing and the potential for misuse were raised as concerns. A range of potential clinical applications was suggested. The public (100%) and professional (74%) participants were positive overall about microneedle technology. Conclusions This exploratory research study captured the views of the eventual end-users of microneedle technology. Microneedle researchers should now reflect on their research and development activities in the context of stakeholder engagement in order to facilitate the transfer of this new technology ‘from bench to bedside.'